2022
DOI: 10.3390/ijerph192114342
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Depression to Suicidal Attempt in Young Adults: The Mediation Effect of Self-Esteem and Interpersonal Needs

Abstract: Background: Depression increases the risk of suicide. Depression and suicide attempts are significantly impacted by low self-esteem and interpersonal needs (i.e., thwarted belongingness (TB) and perceived burdensomeness (PB)). More research is required to clarify how these factors affected the change from depression to suicidal attempts, which would dramatically lower the suicide fatality rate. We sought to examine the mediating roles of self-esteem, TB, and PB in Chinese young adults, since previous research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Neurobiological studies have revealed altered brain activity in decision-making regions among adults with a history of suicidal behaviors [ 38 ]. Psychological factors such as negative self-perception, self-doubt, and rumination can further exacerbate indecisiveness and its link to SI [ 39 , 40 ]. Impaired interpersonal relationships also showed a significant correlation with SI, consistent with the interpersonal theory of suicide which suggests that persistent SI is often accompanied by unmet interpersonal needs, including high levels of thwarted belongingness (feeling like a burden to others) and perceived burdensomeness (feeling alienated from others) [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurobiological studies have revealed altered brain activity in decision-making regions among adults with a history of suicidal behaviors [ 38 ]. Psychological factors such as negative self-perception, self-doubt, and rumination can further exacerbate indecisiveness and its link to SI [ 39 , 40 ]. Impaired interpersonal relationships also showed a significant correlation with SI, consistent with the interpersonal theory of suicide which suggests that persistent SI is often accompanied by unmet interpersonal needs, including high levels of thwarted belongingness (feeling like a burden to others) and perceived burdensomeness (feeling alienated from others) [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the data of the World Health Organization, more than 700,000 individuals die of suicide each year worldwide. Suicide has become the fourth main cause of death among people aged 15–29, especially among college students (Liu et al, 2022f ). Suicidal ideation is an early psychological activity of suicide.…”
Section: Introductionmentioning
confidence: 99%
“…It refers to death, suicide, and serious self-harm in an individual’s thoughts or thoughts, including thoughts about plans, steps, and results of suicide (Zortea et al, 2020 ). Compared with traditional media, the Internet and social networking sites that are spread described that suicide and suicide knowledge provides more opportunities, according to a study of Chinese students, suicidal ideation and suicide-related highly relevant social media use behavior, including suicide information, reviews, and forward to commit suicide, or talk about suicide-related content (Liu et al, 2022a , 2022b , 2022c , 2022d , 2022e , 2022f ). Although the vast majority of suicidal ideations do not lead to actual suicidal actions, suicidal ideation is still considered a necessary condition for suicide and attempted suicide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations